1998
DOI: 10.1172/jci3568
|View full text |Cite
|
Sign up to set email alerts
|

Clonal expansion and somatic hypermutation of V(H) genes of B cells from cerebrospinal fluid in multiple sclerosis.

Abstract: The cerebrospinal fluid (CSF) of multiple sclerosis (MS) patients is characterized by increased concentrations of immunoglobulin (Ig), which on electrophoretic analysis shows restricted heterogeneity (oligoclonal bands). CSF Ig is composed of both serum and intrathecally produced components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
162
0
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(181 citation statements)
references
References 43 publications
12
162
0
5
Order By: Relevance
“…B cells, which are found in the CNS compartment, display a limited heavy chain repertoire and also contain dominant clonotypes. These cells show extensive replacement mutations in the B cell receptor genes compatible with repeated antigenic challenges (6)(7)(8)(9)(10). Oligoclonal IgG bands (OCBs) are observed in the lesions and CSF but either to a much lesser extent or not at all in the serum of these MS patients (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…B cells, which are found in the CNS compartment, display a limited heavy chain repertoire and also contain dominant clonotypes. These cells show extensive replacement mutations in the B cell receptor genes compatible with repeated antigenic challenges (6)(7)(8)(9)(10). Oligoclonal IgG bands (OCBs) are observed in the lesions and CSF but either to a much lesser extent or not at all in the serum of these MS patients (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The intrathecal B cell expansion seems to occur early, or even prior to the disease [35,36], and established B cell clones are maintained for several years [37]. The V H genes from intrathecal B cells have undergone somatic hypermutation [38][39][40][41][42], which could favor T cell recognition of Ig Id. The high frequency of mutations, and the predominance of the IgG1 isotype [43], imply that the intrathecal B cell response in MS is antigen-driven and T cell dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the compartmentalisation of the immune response in CNS is underscored by the perpetual intrathecal synthesis of oligoclonal IgG in MS, CNS infections and other immune mediated neurological diseases, including SPS (Owens 2006;). CSF T and B cells from MS patients have been reported to be clonally expanded (Oksenberg 1990;Wucherpfennig 1992;Qin 1998;Colombo 2000;Owens 1998Owens , 2003Obermeier 2008) One of the major issues in understanding the pathophysiology of human autoimmune diseases is to identify the target antigens that drive the clonal expansion of autoreactive T cells. In paper II we showed that the synthesis of GAD65 IgG antibodies in SPS is oligoclonal and mediated by a stable population of affinity maturated B cell clones, suggesting that these antibodies are produced by B cells having received T cell help.…”
Section: The Relevance Of Csf Lymphocytes In the Studies Of Ms And Spsmentioning
confidence: 99%